Effectiveness of Social Media-Based E-Learning In Enhancing Business Simulation Understanding: A Case of Edugate - Salima Fadhilatus Sholihah; Istyakara Muslichah; Dim Zarita Suryanugraha (Journal of Research in Social Science and Humanities, 2026)
This study aims to analyze the effectiveness of social media as an instructional support tool in enhancing students’ understanding of a Business Simulation Game. The increasing integration of digital platforms in higher education has encouraged the use of social media as a supplementary learning medium. However, empirical evidence regarding its effectiveness in supporting simulation-based training remains limited. Therefore, this study examines whether social media-based learning contributed to improved learning outcomes and explores students’ learning experience of its implementation, grounded in the Technology Acceptance Model (TAM). The research employs a mixed-method approach involving 125 university students who participated in the competition. Quantitative data were collected through pre-test and post-test assessments as well as Likert-scale questionnaires, while qualitative data were obtained from open-ended responses. The data were analyzed using descriptive analysis, instrument validity and reliability testing, and N-Gain score analysis. The results indicate an increase in post-test scores compared to pre-test results, reflecting improved understanding after the implementation of social media-based instructional support. In addition, students expressed positive learning experience and perception in term of TAM. These findings confirms that social media can function effectively as a supplementary tool in Business Simulation Game competition.